Usage of Data Mining Techniques for combating cyber security (International Journal of Engineering and Computer Science, 2017)
Cybersecurity is concerned with protecting computer and network system from corruption due to malicious software including Trojan horses and virus. Security of our network system is becoming imperative as massive sensitive information is transmitted across the network. In this research paper, data mining application for cybersecurity is highly explored. We discussed various cyber-terrorism or attack committed across the network such as malicious intrusion, credit card fraud, identity thefts, and infrastructure attack. Data mining techniques such as classification, anomaly, link analysis and soon are being applied to detect or prevent the aforementioned cyber-terrorism or attack. Recommendations were made and suggestions for further study was indicated are amazingly valuable in finding security breaks